(untitled) (Ameghiniana, 2021)
This work describes two new materials corresponding to Pachybiotherium illuminatum, a microbiotheriid from Pinturas Formation (early Miocene, Santa Cruz Province, Argentina) previously reported at the lower levels of the Formation on Portezuelo Sumich Sur, now recorded in lower levels of Portezuelo Sumich Norte and the possibly upper levels of Los Toldos Sur localities. The new specimens offer a better understanding of P. illuminatum upper molars morphology and, if the level assignation was correct, allow us to argue that 1) P. illuminatum is reported for the first time as appearing on a typical Santacrucian fauna; 2) the “Pinturan” and Santacrucian faunas at the Río Pinturas localities are more similar than previously reported; 3) the biochron of the species is extended.